Faktor Yang Berpengaruh Terhadap Kesehatan Reproduksi Pada Pekerja Wanita Di PT. Maruki International Indonesia - Widya Hastarina Djaya; A. Multazam; Ella Andayanie (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
There were 56,051 cases of reproductive health disorders recorded among female workers in Indonesia. The age range of workers experiencing reproductive system disorders was highest in the 25-30 year age group, with 10.8% of fatal cases for female workers during the period 2019 to 2021, so researchers were interested in studying more deeply about